'My coupons are like gold': experiences and perceived outcomes of low-income adults participating in the British Columbia Farmers' Market Nutrition Coupon Program. Issue 2 (12th February 2022) - Caron-Roy, Stéphanie; Sayed, Sayeeda Amber; Milaney, Katrina; Lashewicz, Bonnie; Dunn, Sharlette; O'Hara, Heather; Leblanc, Peter; Fournier, Bonnie; Raine, Kim D; Elliott, Charlene; Prowse, Rachel JL; Olstad, Dana Lee
Abstract: Objective: The British Columbia Farmers' Market Nutrition Coupon Program (FMNCP) provides low-income households with coupons valued at 21/week for 16 weeks to purchase healthy foods in farmers' markets. Our objective was to explore FMNCP participants' experiences of accessing nutritious foods, and perceived programme outcomes. Design: The current study used qualitative description methodology. Semi-structured interviews were conducted with FMNCP participants during the 2019 farmers' market season. Directed content analysis was used to analyse the data, whereby the five domains of Freedman et al. 's framework of nutritious food access provided the basis for an initial coding scheme. Data that did not fit within the framework's domains were coded inductively. Setting: One urban and two rural communities in British Columbia, Canada. Participants: Twenty-eight adults who were participating in the FMNCP. Results: Three themes emerged: autonomy and dignity, social connections and community building, and environmental and programmatic constraints. Firstly, the programme promoted a sense of autonomy and dignity through financial support, increased access to high-quality produce, food-related education and skill development and mitigating stigma and shame. Secondly, shopping in farmers' markets increased social connections and fostered a sense of community. Finally, participants experienced limited food variety in rural farmers' markets, lack of transportation and challenges with redeeming coupons. Conclusions: Participation in the FMNCP facilitated access to nutritious foods and enhanced participants' diet quality, well-being and health. Strategies such as increasing the amount and duration of subsidies and expanding programmes may help improve participants' experiences and outcomes of farmers' market food subsidy programmes.